2003
DOI: 10.1038/sj.cgt.7700617
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of intravenous delivery of lipoplexes containing the interferon-β gene and poly I: poly C in a murine lung metastasis model

Abstract: We have evaluated and compared the efficacy of systemic administration of lipoplex formulations containing plasmids encoding IFN-b or IFN-g, and a synthetic double-strand RNA poly I:poly C (pI:pC), a type I IFN inducer, in a lung metastasis model in which colon carcinoma CT-26 cells were inoculated intravenously into immunocompatible mice. Injection of lipoplexes containing plasmid DNA, regardless of IFN gene insertion, stimulated a transient increase in the serum concentration of proinflammatory cytokines suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 51 publications
(60 reference statements)
0
23
0
1
Order By: Relevance
“…In fact, even mammalian DNA becomes a potent immune stimulant when combined with cationic liposomes, as demonstrated recently in a murine tumor model (34). Moreover, cationic liposomes can be used to potentiate immune activation by other TLR agonists, including the TLR3 agonist polyI:C and TLR7/8 agonists such as single-stranded RNA (35)(36)(37)(38).…”
Section: Liposomes Enhance Innate Immune Activation By Nucleic Acidsmentioning
confidence: 96%
“…In fact, even mammalian DNA becomes a potent immune stimulant when combined with cationic liposomes, as demonstrated recently in a murine tumor model (34). Moreover, cationic liposomes can be used to potentiate immune activation by other TLR agonists, including the TLR3 agonist polyI:C and TLR7/8 agonists such as single-stranded RNA (35)(36)(37)(38).…”
Section: Liposomes Enhance Innate Immune Activation By Nucleic Acidsmentioning
confidence: 96%
“…Using these gene expression characteristics of the lung, lipoplex was applied to the prevention of lung cancer metastasis in mice. 68,69) Since the physicochemical properties of pDNA are almost the same, irrespective of the encoding cDNA for the therapy, targeting technologies are especially required for their broad clinical application.…”
Section: Cationic Liposomes For Gene Delivery Following the Systemic mentioning
confidence: 99%
“…13 Bauerschmitz et al 14 showed that modified adenovirus was more efficient than native virus at impeding growth of tumors. Additionally, Sakurai et al 15 showed systemic, i.v. delivery of IFNb or IFNg lipoplexes to be effective prophylactically as well as therapeutically against colon carcinoma lung metastases.…”
Section: Introductionmentioning
confidence: 99%